Difficulties of using the Newton Educational Platform for Male and Female Mathematics Teachers in the Primary Stage (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the difficulties of using the Newton educational platform for male and female mathematics teachers in the primary stage. The researcher used the descriptive analytical correlative approach because it is the appropriate approach to the nature and objectives of the research. The research community consists of mathematics teachers in the primary stage in Diyala Governorate - Baquba District, for the academic year (2021-2022), and their number is (877) teachers, and the number of sample members (480) male and female teachers from the schools of Baqubah District. A tool has been prepared to achieve the goal of the current research, which is a questionnaire for the difficulties of using the Newton educational platform for male and female teachers of mathematics, and after the application and data processing using the appropriate statistical means for research, taking advantage of the statistical program (2014 Spss), the results resulted in difficulties in using the Newton educational platform for Primary school mathematics teachers. Due to the results, it was concluded that there is a clear unintentional neglect and poor follow-up of the Newton educational platform by the male and female mathematics teachers in the research sample, and the lack of many schools of electronic laboratories to use the Newton educational platform and the time allotted for one class is insufficient to cover the topic of the lesson. According to the research results, the researcher recommended a number of recommendations, including the involvement of educational cadres in development courses on how to use the Newton educational platform in particular and educational platforms in general. The researcher suggested conducting a number of studies for different groups related to the educational process:Determining the difficulties of using the Newton educational platform by mathematics supervisors in the primary stage and proposing solutions to them.Identifying the impact of using the Newton educational platform in primary schools in acquiring mathematical concepts and their relationship to technological development.Studying teachers' attitudes towards using the Newton educational platform in teaching mathematics.4- Making a comparative study between Newton's educational platform and other platforms from the point of view of teachers in acquiring mathematical concepts.